Traditional eye medicine use among ophthalmic patients attending a secondary health care center in Southeast Nigeria (Port Harcourt Medical Journal, 2017)
Introduction: The perceived high cost of eye care services has been implicated as one of the reasons for the use of traditional eye medications (TEMs) in the country. Other factors including distance, tradition, ignorance, and failure of medical treatment among others have also been documented as determinants of TEM use. TEMs constitute a wide range of unorthodox therapies utilized for treatment of ocular disorders. They have been reported to have no beneficial effect rather causing more harm than good.Aim: This study sought to determine the prevalence, types, and ocular indications for TEM use in the study population.Methods: This was a cross-sectional study in which a structured questionnaire was used to collect relevant data from consecutive patients attending the eye clinic during the study.Results: At a prevalence of 15.8%, the highest use of TEM was noted among artisans, those in the seventh decade of life, with low level of education, ocular complaints of poor vision, and illness of